Recent advances in supported acid/base ionic liquids as catalysts for biodiesel production - Zhang, Qidi; Hu, Yuxuan; Li, Siying; Zhang, Meiqi; Wang, Yangang; Wang, Ziheng; Peng, Yixiang; Wang, Meng; Li, Xi; Pan, Hu (Frontiers in Chemistry, 2022)
Biodiesel is considered as a potential substitute for fossil diesel because of its unique environmentally friendly and renewable advantages. The efficient and durable heterogeneous catalysts are vital to the greenly and efficiently driving the biodiesel production process. The ionic liquid functionalized materials, possessing the characteristics of both homogeneous and heterogeneous catalysts, are one of promising substitutions to conventional homogeneous acid/base catalysts for producing biodiesel. This mini review focuses on recent advances in supported acid/base ionic liquids to synthesize ionic liquid functionalized materials for producing biodiesel. The methods of immobilizing ionic liquids on supports were summarized. The merits and demerits of various supports were discussed. The catalytic activities of the ionic liquid functionalized materials for biodiesel production were reviewed. Finally, we proposed the challenges and future development direction in this area.